Risk Factors Associated with Perinatal Mortality in West Java, Indonesia (Study in Karawang, Garut , Indramayu and Tasikmalaya City) - Luh Nik Armini; Iin Prima Fitriah; Wahidah Sukriani; Sutriningsih; Farid Husin; Herman Susanto; Dany Hilmanto (Institute of Medico-legal Publications Pvt Ltd, 2021)
Perinatal mortality is the death of a baby born at 28 weeks of gestation until less than 7 days afterbirth. Perinatal mortality is used to attribute causes of infant death to obstetric events such as stillbirth andinfant mortality in the first week of life. The purpose of this study was to describe the causes, periods, andrisk factors that influence perinatal mortality . The design of this study is the Sequential Explanatory MixedMethods , Research Quantitative designed with analytical methods conducted cross-sectiona l. Sampling wasdone by total sampling. 396 research sample data. The subjects in this study were parents, health workerswho were involved and understood about the causes of perinatal death and the person in charge of recordingand reporting perinatal deaths in health care facilities . 60.6% of the fatalities that occurred were preventabledeaths. Perinatal deaths that often occur are still births and early neonatal. At 2-21% perinatal kamtian, it iscarried out by non-health workers. The risk factors that affect perinatal mortality are pregnancy distance (p= 0.04 ) and comorbidities (p = 0.019).